Particulate mercury in ambient air in Shanghai, China: Size-specific distribution, gas–particle partitioning, and association with carbonaceous composition. (July 2018) - Han, Deming; Zhang, Jiaqi; Hu, Zihao; Ma, Yingge; Duan, Yusen; Han, Yan; Chen, Xiaojia; Zhou, Yong; Cheng, Jinping; Wang, Wenhua
Abstract: Mercury (Hg) has a complex atmospheric transformation cycle and acts as a global pollutant. Size-specific particle bound mercury (PBM) was implemented in different functional (industrial, urban and suburban) areas in Shanghai, China. The total concentration of 13-staged PBM (rang of 0.01–18.0 μm) varied of 99.0–611 pg/m 3, with an average value of 318 ± 144 pg/m 3 . The Gaoqiao petrochemical industry (GQPI) site showed the highest concentrations, whereas the suburban Shanghai Jiao Tong University (SJTU) displayed the lowest. The PBM in nucleation, accumulation and coarse modes were 7.63–96.7, 69.5–455, and 9.43–176 pg/m 3, respectively, and the fractions of 0.56–1.00 and 0.32–0.56 μm were the two most abundant. Both OC and EC displayed unimodal distribution patterns (peak of 0.56–1.00 μm) at GQPI, while bimodal distributions were observed at urban and suburban sites. Statistically positive correlations between the overall PBM and the corresponding PM and carbonaceous compounds (r = 0.38–0.54, p < 0.01), indicating their similar origins and OC/EC enhanced gaseous mercury forming PBM. The gas–particle partition model predicted gaseous oxidized mercury (GOM) were 253 ± 133, 237 ± 122, and 257 ± 144 pg/m 3 for GQPI, SAES and SJTU, respectively. The particle proportions of divalent mercury in the fraction of 0.32–1.00 μm were substantial (>80%), but smaller (<50%) for nucleation and coarse modes. The fraction of 9.90–18.00 μm occupied nearly 50% of the overall dry deposition fluxes of mercury. These finding highlight the emissions from different mercury and OC/EC origins, caused different size-specific distributions of PBM, which further affect their gas-particle partitioning and dry deposition of mercury species. Graphical abstract: In the atmosphere, gaseous elemental mercury (GEM) is the dominant atmospheric mercury species (>90% of the total), it could eventually be removed from atmosphere through oxidating to more water soluble divalent species, e.g. reactive gaseous mercury (RGM) and particle bound mercury (PBM). These oxidized mercury can be reduced by various atmospheric reductants in aerosols, fog, cloud and interfaces, ultimately affecting their atmospheric fate as well as the biogeochemical cycle.Image 1 Highlights: The size-specific distributions of PBM, OC and EC were measured in different functional areas. OC and EC enhanced gaseous mercury to shape PBM in accumulation mode. Gas-particle partitioning of divalent mercury were investigated in different size aerosol. The dry deposition fluxes of PBM showed apparent particle size distribution pattern.